Lee Lawrie papers - Lawrie, Lee, 1877-1963.
General and family correspondence, sculpture commission files, biographical file, and other papers documenting Lawrie's career as a sculptor whose works were an integral part of public buildings, monuments, and churches throughout the United States. Includes correspondence between Lawrie and architect Bertram Grosvenor Goodhue with whom he collaborated on sculptures for St. Thomas' Church and Church of the Heavenly Rest, New York, N.Y., and material relating to his design of the memorial tomb for Goodhue at the Chapel of the Intercession, also in New York. Other sculpture commissions documented include works for the National Academy of Sciences building, Washington, D.C., and the Nebraska State Capitol in Lincoln. Other projects include works for the Cathedral of St. John the Divine and the International Building at Rockefeller Center, New York, N.Y.; United States Military Academy, West Point, N.Y.; Los Angeles Public Library; Bok Tower, Lake Wales, Fla.; Louisiana State Capitol in Baton Rouge; Harkness Memorial Tower, Yale University, New Haven, Conn.; Memorial Bridge, Harrisburg, Pa.; and the statue of George Washington at the Washington Cathedral, Washington, D.C.
Also includes material on Lawrie's roles as consultant in sculpture to the Board of Design for the New York World's Fair, 1939, to the U. S. Architect of the Capitol during the renovation of the House and Senate chambers, and to the American Battle Monuments Commission, and as a member of the U.S. Commission of Fine Arts, 1933-1937 and 1945-1950.
Library of Congress Prints and Photographs Division.
Sculptor. Full name: Lee Oskar Lawrie.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Goodhue, Bertram Grosvenor, -- 1869-1924 -- Correspondence; Goodhue, Bertram Grosvenor, -- 1869-1924 -- Tomb; Washington, George, -- 1732-1799 -- Statues; American Battle Monuments Commission; Cathedral of St. John the Divine (New York, N.Y.); Chapel of the Intercession (New York, N.Y.); Church of the Heavenly Rest (New York, N.Y.); Los Angeles Public Library; Louisiana State Capitol (Baton Rouge, La.); National Academy of Sciences (U.S.) -- Buildings; Nebraska State Capitol (Lincoln, Neb.); Rockefeller Center -- Buildings; St. Thomas' Church (New York, N.Y.); United States. -- Architect of the Capitol; United States. -- Commission of Fine Arts; United States Capitol (Washington, D.C.); United States Military Academy -- Buildings; Washington Cathedral; Yale University -- Buildings; Bok Tower (Lake Wales, Fla.); Bridges -- Pennsylvania -- Harrisburg; Church buildings -- New York (State) -- New York; Library buildings -- California -- Los Angeles; Public buildings -- Connecticut -- New Haven; Public buildings -- Florida -- Lake Wales; Public buildings -- Louisiana -- Baton Rouge; Public buildings -- Nebraska -- Lincoln; Public buildings -- United States; Sculpture -- United States; Sculpture, American; Bok Tower (Lake Wales, Fla.); Baton Rouge (La.) -- Buildings, structures, etc; Lincoln (Neb.) -- Buildings, structures, etc; New York (N.Y.) -- Buildings, structures, etc; United States -- Capital and capitol; Washington (D.C.) -- Buildings, structures, etc; Sculptors